Real time quantification of dangerousity in soccer using spatiotemporal tracking data - Link, D.; Lang, S.; Seidenschwarz, P. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This study describes an approach to quantification of attacking and defensive performance in football. Our procedure determines a quantitative representation of the probability of a goal being scored for every point in time at which a player is in possession of the ball - we refer to this as dangerousity. The calculation is based on the spatial constellation of the player and the ball, and comprises of the four components Zone, Control, Pressure and Density. We use these metrics to analyse individual actions in a match, to describe passages of play and to characterise the performance and efficiency of teams over the season.